2022
DOI: 10.1097/gox.0000000000004075
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Keloids: A Meta-analysis of Intralesional Triamcinolone, Verapamil, and Their Combination

Abstract: They can occur in many places on the body; however, the chest, shoulders, and earlobes are the most common locations. 1 Although there are many treatment modalities in use, none have been determined to be the gold standard of care. Keloid therapy continues to be an emphasized area of research to attempt to find the best treatment possible. There have been numerous treatment modalities attempted in the clinical setting, ranging from noninvasive to surgical. These include pressure dressings, silicone gel sheetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 30 publications
2
19
0
2
Order By: Relevance
“…Triamcinolone acetonide has become a wellestablished anti-keloid corticosteroid with low systematic toxicity since it was reported by Griffith (1966). It is an effective anti-inflammatory agent that decreases fibroblast proliferation and collagen synthesis (Klomparens and Simman, 2022). Lim et al (2007) reported keloid formation in four patients after syndactyly reconstruction with an acceptable result after two intralesional triamcinolone acetonide injections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Triamcinolone acetonide has become a wellestablished anti-keloid corticosteroid with low systematic toxicity since it was reported by Griffith (1966). It is an effective anti-inflammatory agent that decreases fibroblast proliferation and collagen synthesis (Klomparens and Simman, 2022). Lim et al (2007) reported keloid formation in four patients after syndactyly reconstruction with an acceptable result after two intralesional triamcinolone acetonide injections.…”
Section: Discussionmentioning
confidence: 99%
“…Drug injection has always been a major adjuvant therapy. The commonly used keloid injection drugs include corticosteroids (triamcinolone acetonide and betamethasone), 5fluorouracil, verapamil and bleomycin (Kim et al, 2020;Klomparens and Simman, 2022;Sun et al, 2021). Successful outcomes after methotrexate administration have also been reported, although close monitoring is required because of the various systematic side effects of this drug (Kong et al, 2012;Muzaffar et al, 2004;Tolerton and Tonkin, 2011;Tonkin et al, 2008;Widerberg and Rosberg, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include dressings, silicone gel sheeting, intralesional injections, topical application of mitomycin C, radiotherapy, cryotherapy, and surgical excision. 3 Considering the high likelihood of recurrence following keloid excision, the medical field is extensively exploring various treatment options to discover the most effective intervention. 4 Corticosteroids, notably triamcinolone, are typically the initial choice in the treatment of keloids.…”
Section: Introductionmentioning
confidence: 99%